Healthcare Efficiency as a Wellbeing Factor in the Siberian Federal District; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Kudelina O. Olga (2017, 2017)
Title screen